2007
DOI: 10.1002/ceat.200600356
|View full text |Cite
|
Sign up to set email alerts
|

Model Assessment for the Prediction of Mass Transfer Coefficients in Liquid‐Liquid Extraction Columns

Abstract: A large number of theories are reported in the literature for the calculation of individual mass transfer coefficients and each has a well defined application range, which depends on the nature of the continuous and the dispersed phases. Each theory is also based on a different transfer mode, e.g., the dispersed phase depends essentially on the drop behavior, which is directly related to the drop size. However, an accurate determination of the overall mass transfer coefficient depends upon the choice of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…At the top part of the column, large droplet behaves as an oscillating one with an extremely high mass transfer coefficient 55 . If the drop decreases in size at a critical rate, oscillation in the resultant droplet disappears while internal circulation starts to build up, enhancing the rate of mass transfer within the dispersed phase 56 . At the bottom part of the column, the droplet size is further reduced and becomes internally stagnant, resulting in a rigid drop which has low mass transfer coefficient 48,57 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the top part of the column, large droplet behaves as an oscillating one with an extremely high mass transfer coefficient 55 . If the drop decreases in size at a critical rate, oscillation in the resultant droplet disappears while internal circulation starts to build up, enhancing the rate of mass transfer within the dispersed phase 56 . At the bottom part of the column, the droplet size is further reduced and becomes internally stagnant, resulting in a rigid drop which has low mass transfer coefficient 48,57 .…”
Section: Resultsmentioning
confidence: 99%
“…55 If the drop decreases in size at a critical rate, oscillation in the resultant droplet disappears while internal circulation starts to build up, enhancing the rate of mass transfer within the dispersed phase. 56 At the bottom part of the column, the droplet size is further reduced and becomes internally stagnant, resulting in a rigid drop which has low mass transfer coefficient. 48,57 Therefore, the mass transfer coefficient reported in the literature 45,58 is usually inversely proportional to the energy input.…”
Section: Evaluation Of the Mass Transfer Coefficient Modelsmentioning
confidence: 99%
“…The relative Reynolds number, Re, an important factor in determining the mass transfer coefficient, 46,47 was also calculated using eq 8. Figure 4d shows that the relative Reynolds number varies from 30 to 60 in one pulsation period, and there is no noticeable change in the range of relative Reynolds number with increasing the pulsation intensity.…”
Section: Drop Velocity 411 Effect Of Pulsation Intensitymentioning
confidence: 99%
“…Venkatanarasaiah and Varma reported that the mass transfer coefficient depends linearly on the drop size and consequently on the dispersed phase holdup, which is a function of the pulse velocity . Various attempts have been made for designing liquid–liquid extraction columns based on the laboratory-scale single-drop experiment. This approach primarily focuses on the determination of the overall mass transfer coefficient based on the dispersed phase drop formation, breakage, coalescence, and sedimentation. Many times, ReDrop , and the drop population balance , modeling approach have been used to arrive at the design of equipment.…”
Section: Introductionmentioning
confidence: 99%